Intraspecific variation and emendation of Hannaella kunmingensis - Dayo-Owoyemi, Ifeloju [UNESP]; Rodrigues, Andre [UNESP]; Landell, Melissa F.; Valente, Patricia; Mueller, Ulrich G.; Ramos, Jesus Pais; Pagnocca, Fernando C. [UNESP] (Springer Nature, 2013)
In order to investigate the intraspecific variability in Hannaella kunmingensis, 11 isolates, including the type strain, were analyzed for their morphological and biochemical traits. The combined internal transcribed spacer region (ITS), D1/D2 domains of the large subunit rDNA (LSU), and cytochrome b gene were examined using phylogenetic and parsimony network analyses. Our investigations revealed differences in colony morphology as well as differences in 31 out of 64 phenotypic characteristics examined, including growth in lactose, vitamin free medium, xylitol, L-arabinitol, and nitrite. Growth in the presence of 0. 1 % cycloheximide was also highlighted in H. kunmingensis. All the 11 strains were conspecific in the LSU; however, variations of about 2. 5 % were found in the ITS while isolate CBS 8356 exhibited a 27. 3 % divergence from the other strains in the cytochrome b gene. Parsimony network analysis revealed the existence of three haplotypes among the H. kunmingensis strains studied but excluded CBS 8356 from the network connecting these haplotypes. This study contributes to the knowledge of the intraspecific diversity of H. kunmingensis. To accommodate such intraspecific variations, an emendation of the species diagnosis is proposed. © 2012 German Mycological Society and Springer.